(3EOQGI GdJfejI (B:s (3GdCSS , GdfXQjGJ , GdJWHjbGJ GdYedjI (B/s - (3GdYhGedI, fGFd YHO GdMGaXs ((3YeGf(B: s (3OGQ RgQGf(B, s, 2010)
(3eaghe GOQGI GdJfejI , fXQjGJ GdJfejI h GdJfejI GdGOGQjI , GdJNWjW GdJfehj h GdGWGQ GdeDSSj h GdJfXjej ddJfejI , Jehjd GdJfejI , GdJfejI GdeMdjI h GdJfejI aj GdGSdGe h CNjQG bVGjG JfehjI eJNUUIs
(3edMb U(B.189 (3; eQGLY U(B.203s
Keywords: (3GdJNWjW GdJfehjs; (3GdJfejIs; (3GdJfejI GdEOGQjIs